HIV infection and the implication for COVID‐19 vaccination - Tope Oyelade; Reynie Purnama Raya; Kamaluddin Latief (Public Health Challenges, 2022)
Abstract Human immunodeficiency virus (HIV) is associated with altered cellular and humoral immune response, especially in patients with an untreated or chronic infection. This may be due to direct and/or indirect HIV viral activities resulting in T‐ and B‐cells dysfunctions. Although still unclear, various studies have proposed that HIV infection may exacerbate the clinical outcomes of COVID‐19. Indeed, COVID‐19 vaccines were developed in record time and have been shown to reduce the severity of COVID‐19 in the general population. These vaccines were also earmarked as a solution to global disruptions caused by the COVID‐19 pandemic. HIV infection has been reported to reduce the efficacy of various other vaccines including those used against Streptococcus pneumoniae, Clostridium tetani, and influenza viruses. However, current guidelines for the administration of available COVID‐19 vaccines do not account for the immune‐compromised state of people living with HIV (PLWH). We discuss here the potentials, nature, and implications of this HIV‐induced dampening of the humoral immune response on COVID‐19 vaccines by first reviewing the literature about efficacy of previous vaccines in PLWH, and then assessing the proportion of PLWH included in phase III clinical trials of the COVID‐19 vaccines currently available. The clinical and public health implications as well as suggestions for governments and non‐governmental organizations are also proposed in the context of whether findings on the safety and efficacy of the vaccines could be extended to PLWH. Impacts The human immunodeficiency virus (HIV) is characterized by attenuated humoral immunity that may reduce the efficacy of vaccines in people living with HIV (PLWH). Vaccination against the SARS‐CoV‐2 infection remains the main public health answer to the COVID‐19 pandemic. Although no significant safety concerns have been raised regarding the COVID‐19 vaccines in PLWH, the efficacy of these vaccines in PLWH has not received due attention. Indeed, phase III clinical trials for the safety and efficacy of COVID‐19 vaccines involved a significantly low number of PLWH. There are major gaps in knowledge on the efficacy of COVID‐19 vaccines in PLWH and until further research is carried out, PLWH should be prioritized along with other at‐risk groups for repeated vaccination and safeguard.